(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
The main problems of Indonesian capture fisheries are overfishing, fishermen poverty, and degradation of marine ecosystems in which there are complex relationships. Therefore, the research in October 2018-October 2019 aims to determine essential variables of the national capture fisheries system that can assist the government in the making capture fisheries policies more effectively by using method and software MICMAC (Matrice d’Impacts Croisés-Multiplication Appliquee à un Classement). The results showed that there were 28 variables of national capture fisheries system that consist of 5 categories, namely economy, policy, social-cultural, environment, and science and technology. Structural analysis shows that variables with the most substantial influence based on Matrix of Direct Influences (MDI) and Matrix of Indirect Influences (MII) are the production of capture fisheries, IUU fishing, policy on capture fisheries, and cost of fishing. Meanwhile, variables with the most substantial dependence based on MDI and MII are the fish stock and fisheries industry. Also, the displacement map from MDI to MII is only occurred within the quadrant (out of four quadrants), but the variable of government subsidy that changes from relay variable quadrant to dependent variable quadrant.